Marketing Analysis of Frozen Mackerel Fish Products in Danish Kitchen UMKM - Riani, Maria Ulfah (Agrikan Jurnal Agribisnis Perikanan, 2024)
The Danish Kitchen UMKM business scale is still very small compared to frozen food which already has its own factory, which of course means production costs are high due to the small amount of production. The aim of the research carried out at Danish Kitchen is to find out effective marketing analysis in terms of mix, chain, margin and farmer share so that it is hoped that it can compete with frozen food made from beef and chicken as well as with food products produced by existing factories. have a name in the market in the future. The method used in this research is the first field study method which includes observation and interviews. The second method used is the literature study method which includes analysis of the marketing mix, marketing channels, marketing margin and farmer's share. The marketing mix for Danish Kitchen frozen food products from the strongest to the weakest, namely product, place, promotion and finally price. There are two marketing channels for Danish Kitchen frozen food products, namely the first from the producer directly to the final consumer and the second marketing channel, namely from the producer then to the wholesaler and finally to the final consumer. The marketing margin for Danish Kitchen frozen food products is IDR. 5,000 and the farmer's share of Danish Kitchen frozen food products is 87.5% - 90%. It can be said to be efficient because it is greater than 50%